BAHAYA LIMBAH INDUSTRI TERHADAP KEBERLANGSUNGAN HIDUP MANUSIA - Ardian Hangga Kelana; Titia Erika Sarlota Awom; Saul Weipsa; Yekson Soll; Evellyne Binsyowie Sandhiya Mandosir (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity (PKM) aims to provide information and knowledge about "The Dangers of Industrial Waste to Human Survival" at SMAS YPK Diaspora Kotaraja Jayapura. This community service uses a participatory approach that actively involves students in every stage of the activity. The design of the activity follows the Community-Based Participatory Research (CBPR) model which emphasizes collaboration between lecturers, teachers, and students at SMAS YPK Diaspora Kotaraja Jayapura in identifying problems, planning, implementation, and evaluation. During the activity, participants participated enthusiastically and were committed to protecting the school environment, residence, and community from the dangers of industrial waste to human survival